Nitrogen and Carbon Cycling in a Grassland Community Ecosystem as Affected by Elevated Atmospheric CO2 - H. A. Torbert; H. W. Polley; H. B. Johnson (International Journal of Agronomy)
Increasing global atmospheric carbon dioxide (CO2) concentration has led to concerns regarding its potential effects on terrestrial ecosystems and the long-term storage of carbon (C) and nitrogen (N) in soil. This study examined responses to elevated CO2 in a grass ecosystem invaded with a leguminous shrub Acacia farnesiana (L.) Willd (Huisache). Seedlings of Acacia along with grass species were grown for 13 months at CO2 concentrations of 385 (ambient), 690, and 980 μmol mol−1. Elevated CO2 increased both C and N inputs from plant growth which would result in higher soil C from litter fall, root turnover, and excretions. Results from the incubation indicated an initial (20 days) decrease in N mineralization which resulted in no change in C mineralization. However, after 40 and 60 days, an increase in both C and N mineralization was observed. These increases would indicate that increases in soil C storage may not occur in grass ecosystems that are invaded with Acacia over the long term.